Factors Related to Patient Safety Culture in the Operating Room - Devi, Ni Luh Putu Lusiana; Setiabudi, I Ketut; Wahyuningsih, Luh Gde Nita Sri; Putri, I Gusti Ayu Nandita Arta (Indonesian Journal of Global Health Research, 2024)
Patient safety culture remains a major concern globally, particularly in anesthesia and surgical services. Considering that surgical and anesthesia services involve various types of invasive procedures that can cause death or complications. This study aims to determine factors related to patient safety culture in the operating room. This quantitative correlation research involved 56 nurses and nurse anesthetists at Hospital A and Hospital B. The sampling technique used was cluster sampling-total sampling. Each respondent has filled out a structured questionnaire via Google Form and has been analyzed using descriptive statistics, chi-square test. To ensure the validity and reliability of the questionnaire, content validity was assessed by experts in the field to confirm that the questions covered all relevant aspects of patient safety culture in the operating room. Reliability was evaluated using Cronbach's alpha, which demonstrated a high level of internal consistency. These measures ensured that the questionnaire accurately and reliably captured the factors related to patient safety culture among the participating nurses and nurse anesthetists. This research found that patient safety culture in the operating room was in the poor category as many as 30 nurses and nurse anesthetists (54%). Training and knowledge about patient safety factors were associated with patient safety culture in the operating room (p= 0.045 and p<0.001). Support from hospital management is very necessary to be able to accommodate all staff in the operating room in implementing an optimal patient safety culture through outreach and training.